Pengaruh Pajak, Ukuran Perusahaan, Exchange Rate dan average Terhadap Transfer Pricing - Choirunnisa, Tarisa Adinda; Abbas, Dirvi Surya; Hidayat, Imam; Sriyanto, Sriyanto (Jurnal Ilmiah Ilmu Manajemen, 2022)
The purpose of this study was to determine the effect of tax, firm size, tunneling incentive and leverage on transfer pricing in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange. The research time period used is 5 years, namely the 2015-2021 period. The population of this study includes all food and beverage companies listed on the Indonesia Stock Exchange for the period 2015-2021. The sampling technique used was purposive sampling technique. Based on the predetermined criteria, 6 companies were obtained. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analytical method used is panel data regression analysis. The results show that tunneling incentives have an effect on positive on transfer pricing, while taxes, firm size, and leverage have no effect on transfer pricing.